Quantitative trait loci analysis of grain appearance in Oryza sativa L. ‘Emi-no-kizuna’ - Nagaoka, Ichiro (Breed Sci, 2017)
A quantitative trait locus (QTL) analysis was conducted on grain appearance in Emi-no-kizuna, a rice cultivar that has superior and stable appearance of the brown rice grain and high tolerance to high temperature stress, by using F(3) lines derived from Emi-no-kizuna and Tomohonami. The investigation was performed 2013 and 2015. In summer 2013 the air temperature was higher and the larger differences in grain appearance were observed. In the QTL analysis, a highly contributing locus, qGA8, was detected at the end of the short arm of chromosome 8. Because trends of reduced the occurrence of white immature kernel and increased the percentage of perfect grain were observed in Emi-no-kizuna genotype in both years, qGA8 is likely to be an important QTL that is dominant in the superior grain appearance of Emi-no-kizuna. Also, qGA8 was linked to a QTL associated with days to heading. Another QTL, qGA7, associated with grain appearance was detected on chromosome 7 in 2013. Because no negative correlation was found between the genotype of qGA8 and thousand grain weight, it should be possible to breed cultivars that possess Emi-no-kizuna genotype qGA8 without a decrease in thousand grain weight.